Intraoperative Cerebral Glioma Characterization with Contrast Enhanced Ultrasound. (12th June 2014) - Prada, Francesco; Mattei, Luca; Del Bene, Massimiliano; Aiani, Luca; Saini, Marco; Casali, Cecilia; Filippini, Assunta; Legnani, Federico Giuseppe; Perin, Alessandro; Saladino, Andrea; Vetrano, Ignazio Gaspare; Solbiati, Luigi; et al.
Abstract : Background . Contrast enhanced ultrasound (CEUS) is a dynamic and continuous modality providing real-time view of vascularization and flow distribution patterns of different organs and tumors. Nevertheless its intraoperative use for brain tumors visualization has been performed few times, and a thorough characterization of cerebral glioma had never been performed before. Aim . To perform the first characterization of cerebral glioma using CEUS and to possibly achieve an intraoperative differentiation of different gliomas. Methods . We performed CEUS in an off-label setting in 69 patients undergoing surgery for cerebral glioma. An intraoperative qualitative analysis was performed comparing iCEUS with B-mode imaging. A postprocedural semiquantitative analysis was then performed for each case, according to EFSUMB criteria. Results were related to histopathology. Results . We observed different CE patterns: LGG show a mild, dotted CE with diffuse appearance and slower, delayed arterial and venous phase. HGG have a high CE with a more nodular, nonhomogeneous appearance and fast perfusion patterns. Conclusion . Our study characterizes for the first time human brain glioma with CEUS, providing further insight regarding these tumors' biology. CEUS is a fast, safe, dynamic, real-time, and economic tool that might be helpful during surgery in differentiating malignant and benign gliomas and refining surgical strategy.